Victimization of Women in Prisons: A Comparative Analysis of India and Indonesia - Parul, Parul; Luvleen, Luvleen (Brawijaya Law Journal, 2020)
Prisons have become a world of their own, and women are its new citizens. There have been many studies on incarcerated as a result of the growing numbers of women in prisons, and feminist studies. The on-going reconstruction of literature on this subject has given rise to a new question as to whether we should consider women in prisons, as victims in need of protection, or has this narrative changed?This article unfolds as follows: The first section delves into the conceptual development of sexual rights of women in the international sphere, focusing specifically on women in prisons. Subsequently, the second section analyzes in detail various studies, articles and news reports on the subject of sexually abusive treatment of women inmates offering a brief overview of the concerns in India and Indonesia. The methodology adopted for this article is primarily doctrinal, for the comparative analyses of the rights available to women inmates under various national and international legal instruments.